To Explore the Influence of Debt on Financial Risk of Real Estate Enterprises: Empirical test based on PVAR model - Wu, Yuxuan (International Journal of Global Economics and Management, 2024)
It has become urgent to establish the credit evaluation system of real estate enterprises which conforms to the national conditions of China. This paper explores the possible paths that the increase of debt of real estate enterprises affects the financial risk of real estate enterprises, analyzes the relationship between the major factors that affect the financial risk of real estate enterprises, and uses PVAR model to test the above theoretical analysis. The research finds that the increase in the debt ratio of real estate enterprises will have a significant negative impact on the improvement of their long-term solvency, and the factors affecting the financial risk of real estate enterprises are interconnected on the time level. At the same time, when the debt ratio increases, enterprises with higher media attention will accumulate more financial risks.